AMAP organizational structure - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Monitoring and Assessment Program (AMAP), 2002)
Illustation of Arctic Council working group Arctic Monitoring and Assessment Program (AMAP)'s organizational structure presented at the Arctic Councils Senior Arctic Officials meeting in Oulu, Finland, May 15-16 2002.